Exploring the efficacy of explicit encoding and fast mapping in second language vocabulary acquisition among Chinese graduate students - Jingjing Wu; Le Cheng; Xiaowen Zhao (Humanities & Social Sciences Communications)
Abstract This study explores the effects of explicit encoding and fast mapping on English vocabulary acquisition among Chinese graduate students, and comparing the impact of uni-modal and multi-modal environments on learning outcomes. Specifically, it examines these learning methods, considering the semantic relationships of the target vocabulary, the learners’ proficiency in the second language and the integration of various learning modalities. The results reveal that the combination of explicit encoding and fast mapping is most effective in multi-modal settings, particularly in improving the response speed and accuracy for both immediate and delayed tasks. Advanced second language learners benefit more from this combined approach showing better learning outcomes. These findings emphasize the importance of customizing learning strategies based on learners’ linguistic abilities and provide empirical support for the effective integration of various learning strategies. This paper provides new insights into second language vocabulary acquisition, particularly in multi-modal learning strategies. It aims to expand existing vocabulary learning theories and offer empirical evidence for the education of Chinese graduate students.